2021
DOI: 10.1038/s12276-021-00704-w
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell analysis of salt-induced hypertensive mouse aortae reveals cellular heterogeneity and state changes

Abstract: Elevated blood pressure caused by excessive salt intake is common and associated with cardiovascular diseases in most countries. However, the composition and responses of vascular cells in the progression of hypertension have not been systematically described. We performed single-cell RNA sequencing on the aortic arch from C57BL/6J mice fed a chow/high-salt diet. We identified 19 distinct cell populations representing 12 lineages, including smooth muscle cells (SMCs), fibroblasts, endothelial cells (ECs), B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 53 publications
(57 reference statements)
1
24
0
Order By: Relevance
“…Next, we assessed the composition of cells in the aorta as a result of DPP4 inhibition using singlecell RNA sequencing (scRNA-seq) and DPP4 Cellular Indexing of Transcriptomes and Epitopes by Sequencing (CITE-seq) analyses (39). We identified 11 cell types defined by 21 clusters of aortic cells using cell type-specific markers for all major cell types as defined in the literature (40)(41)(42)(43) (Figure 8A, Supplemental Figure S7, and Supplemental Figure S8, A and B). We visualized total Dpp4 mRNA expression levels as well as the levels of DPP4 protein distribution on the cell surface in all cells (Figure 8, B and C).…”
Section: Inhibition Of Dpp4 In the Ldlr -/Mouse Model Of Atherosclero...mentioning
confidence: 99%
“…Next, we assessed the composition of cells in the aorta as a result of DPP4 inhibition using singlecell RNA sequencing (scRNA-seq) and DPP4 Cellular Indexing of Transcriptomes and Epitopes by Sequencing (CITE-seq) analyses (39). We identified 11 cell types defined by 21 clusters of aortic cells using cell type-specific markers for all major cell types as defined in the literature (40)(41)(42)(43) (Figure 8A, Supplemental Figure S7, and Supplemental Figure S8, A and B). We visualized total Dpp4 mRNA expression levels as well as the levels of DPP4 protein distribution on the cell surface in all cells (Figure 8, B and C).…”
Section: Inhibition Of Dpp4 In the Ldlr -/Mouse Model Of Atherosclero...mentioning
confidence: 99%
“…These 3 populations have previously established physiological functions within the kidney. Similarly, the aorta is segregated into subpopulations that regulate different arterial responses at homeostasis and hypertensive states in humans and mice (Kalluri et al, 2019; Zhang et al, 2021). Similar findings exist in a study on the adult human pulmonary artery endothelium in health and disease.…”
Section: Discussionmentioning
confidence: 99%
“…One such modern approach to identify how SRC-IgG differentially influence EC and vSMC would be single-cell sequencing. Two recent articles have thus investigated the relative impact of EC and vSMC in hypertension-induced vascular remodeling [ 43 , 44 ]. In a mouse model of salt-induced hypertension, Zhang et al showed that hypertensive vessels present increased smooth muscle cell populations, partly due to endothelial-to-mesenchymal cell transition [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent articles have thus investigated the relative impact of EC and vSMC in hypertension-induced vascular remodeling [ 43 , 44 ]. In a mouse model of salt-induced hypertension, Zhang et al showed that hypertensive vessels present increased smooth muscle cell populations, partly due to endothelial-to-mesenchymal cell transition [ 44 ]. In a context of systemic sclerosis, single-cell sequencing was used to study immune cell heterogeneity between patients and healthy controls using skin samples [ 45 ], or whole endothelial cell genetic patterns in individuals with or without the disease [ 46 ].…”
Section: Discussionmentioning
confidence: 99%